The Influence of Financial Capital and Human Resource Competency on the Performance of Culinary SMEs in East Jakarta with Digital Marketing as a Moderating Variable - Humaira, Jihan; Mulyana, Asep; Muizu, Wa Ode Zusnita (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This study aims to examine and analyze the influence of financial capital and human resource competence on the performance of culinary SMEs in East Jakarta, with digital marketing as a moderating variable. This research is a quantitative study, using purposive sampling technique with criteria for culinary SMEs, particularly those at the micro level that have gone digital. Data were collected tHuman Resourceough questionnaires. The data analysis method used was multiple linear regression and moderated regression analysis (MRA) using SPSS 26. The results show that there is a positive and significant influence of financial capital on the performance of culinary SMEs in East Jakarta, there is a positive and significant influence of human resource competence on the performance of culinary SMEs in East Jakarta, there is no influence of digital marketing variables in strengthening the relationship between financial capital and the performance of culinary SMEs in East Jakarta, there is no influence of digital marketing variables in strengthening the relationship between Human Resource competence and the performance of culinary SMEs in East Jakarta, and financial capital and Human Resource competence simultaneously influence the performance of culinary SMEs.